MODEL PEMBELAJARAN CONNECTED DALAM PEMBELAJARAN SAINS UNTUK MENINGKATKAN KETERAMPILAN BERPIKIR RASIONAL SISWA MI/SD - Astuti, Rini Nafsiati (Madrasah: Jurnal Pendidikan dan Pembelajaran Dasar, 2011)
Based on observations of how teachers teach science found that the process is still teacher-centered learning, students are not given the opportunity to interact directly with concrete objects and teachers to teach science concepts are fragmented. To overcome these problems is developing an integrated learning model that can enhance the skills of rational thinking. Aspect of rational thinking skills that can be developed include: recall, classify, generalize, and compare as well as aspects of science process skills developed include: observing, classifying, measuring, and interpreting observations. Some of the things that underlies the development of this integrated learning model include: the involvement of students during learning activities, involving the manual and intellectual activities, to attract the attention of students developed a program to play while learning, environment and resources used as a means of learning and a holistic view of children about nature then integreted concepts that can be linked into a coherent whole by using the theme as an umbrella so that the separation between the concept is not so clear.Key words: connected learning, rational thinking, integreted concepts